Li-ion conductor and method for producing same
A garnet-type composite metal oxide Li ion conductor with a modified interface using a low-melting-point eutectic mixture addresses the conductivity challenges in solid electrolytes, achieving high lithium ion conductivity for improved battery performance.
Patent Information
- Application Number
- JP2021545541
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-13
- Filing Date
- 2020-09-08
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2040-09-08
AI Technical Summary
Existing Li-ion secondary batteries, particularly those using solid electrolytes, face challenges in achieving high lithium ion conductivity and stability, which are crucial for applications in mobile devices, hybrid vehicles, and household power storage.
A Li ion conductor with a garnet-type composite metal oxide phase is developed, utilizing a eutectic mixture with a melting point of 600°C or less to modify the interface of the garnet-type composite metal oxide phase, enhancing lithium ion conductivity through improved inter-particle connectivity.
The Li ion conductor exhibits excellent lithium ion conductivity, making it suitable for use as a solid electrolyte in secondary batteries, with conductivity values exceeding 1.0×10⁻⁷ S/cm at room temperature and activation energy of 0.6 eV or less.
Smart Images

Figure 0007606462000002 
Figure 0007606462000003 
Figure 0007606462000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a Li-ion conductor. [Background technology]
[0002] Research and development of Li-ion secondary batteries is being actively conducted for use in portable devices, hybrid and electric vehicles, and home energy storage. Li-ion secondary batteries used in these fields require high safety, long-term cycle stability, and high energy density.
[0003] Among them, all-solid-state batteries using solid electrolytes have been attracting attention due to their high safety. For example, the lithium ion conductor LIC in Patent Document 1 is manufactured by first preparing an ion conductor, then mixing the ion conductor with lithium halide and heating it. For example, the ion conductor Li7La3Zr2O 12 In the case of LLZ-MgSr powder, in which Mg and Sr have been substituted for the elements LLZ-MgSr, raw materials containing each of the elements of LLZ-MgSr (Li2CO3, MgO, La(OH)3, SrCO3, ZrO2, SrCO3, ZrO2) are mixed for 15 hours and sintered at 1000°C for 10 hours to produce the powder, which is then mixed with lithium halide (e.g. LiI) powder to obtain a mixed powder, which is then pressed together with a stainless steel current collector in a press to obtain a green compact, which is then heat-treated at 80°C for 17 hours. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-91788 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a Li-ion conductor that contains a garnet-type composite metal oxide phase and exhibits good lithium ion conductivity, and is different from that in Patent Document 1, and a method for producing the same. [Means for solving the problem]
[0006] The present invention is as follows. [1] A Li-ion conductor having a garnet-type complex metal oxide phase (L) containing Li, La, Zr, and O, which has a diffraction peak at at least one of 2θ=13.8°±1° and 2θ=15.2°±1° in X-ray diffraction measurement using CuKα radiation. [2] The Li ion conductor according to [1], which has a metal-containing phase (K) different from the phase (L), the phase (K) containing a halogen element and Li. [3] Cubic Li in X-ray diffraction measurements using CuKα radiation 6.25 Ga 0.25 La3Zr2O 12 The Li ion conductor according to [1] or [2], wherein a diffraction peak corresponding to 2θ=30.9° is observed at 2θ=30.5° or more and 30.9° or less. [4] The Li ion conductor according to any one of [1] to [3], having a lattice constant of more than 12.95 Å and not more than 13.15 Å. [5] The Li ion conductor according to any one of [1] to [4], having an activation energy Ea of 0.6 eV or less as determined by impedance measurement. [6] Room temperature Li-ion conductivity σ measured by impedance measurement total is 1.0×10 -7 The Li-ion conductor according to any one of [1] to [5], wherein the Li-ion conductor has a viscosity of 1.0 S / cm or more. [7] A method for producing a Li-ion conductor having a garnet-type complex metal oxide phase (L) containing Li, La, Zr and O, comprising connecting interfaces of the garnet-type complex metal oxide phase (L) using a eutectic mixture having a melting point of 600°C or lower. [8] The manufacturing method according to [7], comprising molding a mixture of a eutectic mixture having a melting point of 600°C or less and a garnet-type complex metal oxide containing Li, La, Zr and O, and heat-treating the obtained molding at 600°C or less to connect the interfaces of the phase (L). [9] The method according to [7] or [8], wherein the eutectic mixture is a eutectic mixture of two types of metal halides.
[10] The manufacturing method according to any one of [7] to [9], wherein the eutectic mixture is a eutectic mixture of LiF, ZrCl4, AlCl3, NbCl5 or TaCl5 and LiCl, or a eutectic mixture of LiF and TaF5. Effect of the Invention
[0007] INDUSTRIAL APPLICABILITY The Li-ion conductor of the present invention can provide a good lithium ion conductor, and can be used as a component of an excellent solid electrolyte for secondary batteries. [Brief description of the drawings]
[0008] [Figure 1] 1 is an XRD diffraction chart in Example 1. [Diagram 2] 1 is a drawing-substitute photograph showing SEM observation images of an example and a comparative example. [Diagram 3] FIG. 2 is an enlarged view of an XRD diffraction chart in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] As a result of investigations by the present inventors to obtain a Li-ion conductor exhibiting good lithium ion conductivity, it has become clear that the object of the present invention can be achieved by connecting the interface of the garnet-type complex metal oxide phase (L) with a eutectic mixture having a melting point of 600° C. or less. More specifically, (1) a garnet-type complex metal oxide and a eutectic mixture having a melting point of 600° C. or less may be mixed and heat-treated, or (2) a raw material of the garnet-type complex metal oxide and a eutectic mixture having a melting point of 600° C. or less may be mechanochemically treated.
[0010] The eutectic mixture is preferably a eutectic mixture of two kinds of metal halides, for example, a eutectic mixture of LiF, ZrCl4, AlCl3, NbCl5, or TaCl5 and LiCl, or a eutectic mixture of LiF and TaF5, more preferably a eutectic mixture of LiF, ZrCl4, AlCl3, NbCl5, or TaCl5 and LiCl, even more preferably a eutectic mixture of LiF, AlCl3, NbCl5, or TaCl5 and LiCl, particularly preferably a eutectic mixture of AlCl3, NbCl5, or TaCl5 and LiCl, and most preferably a eutectic mixture of TaCl5 and LiCl.
[0011] In the method (1) of mixing a garnet-type composite metal oxide with a eutectic mixture having a melting point of 600° C. or less and heat-treating the mixture, it is preferable to mix the garnet-type composite metal oxide with a eutectic mixture having a melting point of 600° C. or less and apply pressure to the mixture to produce a molded body such as a pellet, and the heat treatment may be performed by annealing the molded body at 600° C. or less, preferably 500° C. or less, more preferably 300° C. or less, for 5 to 600 minutes, preferably 10 to 480 minutes. The lower limit of the annealing temperature is not particularly limited, but may be, for example, 150° C. or 200° C. In addition, it is preferable that the annealing temperature is 150° C. or more (preferably 200° C. or more) and is not less than (melting point-10° C.) of the eutectic mixture (more preferably not less than the melting point). It is preferable that the annealing is performed under an inert gas atmosphere such as nitrogen or Ar. The pressure during the production of the molded body is, for example, about 300 MPa to 450 MPa. Mixing of the garnet-type complex metal oxide with a eutectic mixture having a melting point of 600° C. or less, molding of the resulting mixture, and annealing are preferably carried out in an environment with sufficiently reduced humidity, such as in a glove box or a dry room, and for example, the dew point temperature is preferably −40° C. to −90° C. In the method (1) above, the ratio of the eutectic mixture to 100 parts by mass of the garnet-type complex metal oxide can be appropriately set depending on the type of eutectic mixture used, the pressure during preparation of the molded body, the annealing conditions, etc., and can be, for example, 15 to 60 parts by mass, and preferably 20 to 50 parts by mass.
[0012] The garnet-type complex metal oxide used in the method (1) may be obtained by mixing the raw materials of the complex metal oxide and firing them at 1000 to 1100°C for about 6 to 12 hours, or by mechanochemically treating the raw materials of the complex metal oxide. The mechanochemical treatment can be performed by compressing and shearing a mixture containing the raw powder of the complex metal oxide under dry conditions.
[0013] The method of mechanochemically treating the raw material of the garnet-type complex metal oxide and the eutectic mixture having a melting point of 600° C. or less in (2) above can be carried out, for example, by compressing and shearing a mixture containing a mixture of the raw material powder of the complex metal oxide and the eutectic mixture having a melting point of 600° C. or less under dry conditions. After the mechanochemical treatment in (2) above, the heat treatment described in (1) above may be further carried out.
[0014] In both of the above (1) and (2), the raw materials for the garnet-type composite metal oxide are at least one of a Li source powder, a La source powder, and a Zr source powder, and further, if necessary, an Al source powder and a Ga source powder. As the Li source powder, the La source powder, the Zr source powder, the Al source powder and the Ga source powder, for example, an oxide, carbonate, hydroxide, chloride, alkoxide, etc. of each metal (Li, La, Zr, Al, or Ga) can be used.
[0015] A preferred Li ion conductor obtained by the above method is a Li ion conductor having a garnet-type complex metal oxide phase (L) containing Li, La, Zr and O, and preferably has a diffraction peak at at least one of 2θ=13.8° and 15.2° in X-ray diffraction measurement using CuKα radiation. In the crystal structure resulting from the diffraction peak at 2θ=13.8° or 2θ=15.2°, the atoms constituting the crystal may be replaced with other atoms, and in that case, the angles at which the diffraction peaks appear may shift within a range of ±1°. The Li ion conductor of the present invention includes such a case, that is, a Li ion conductor having a garnet-type complex metal oxide phase (L) containing Li, La, Zr and O, and has a diffraction peak at at least one of 2θ=13.8°±1° and 2θ=15.2°±1° in X-ray diffraction measurement using CuKα radiation. The range of 2θ=13.8°±1° is preferably 2θ=13.8°±0.5°, more preferably 13.8°±0.3°, and even more preferably 13.8°. The range of 2θ=15.2°±1° is preferably 2θ=15.2°±0.5°, more preferably 15.2°±0.3°, and even more preferably 15.2°.
[0016] The garnet-type complex metal oxide phase (L) containing Li, La, Zr and O is A3B2C3O 12 The position of A in the crystal represented by the formula 3+ and Zr 4+ The C sites and the interstitial sites are occupied by Li + is the phase dominated by Li7La3Zr2O 12 The phase (L) is preferably a cubic crystal. The garnet-type complex metal oxide phase (L) preferably further contains Al and / or Ga. In this case, Li7La3Zr2O 12 Li in + Part of the site is Al 3+ and / or Ga 3+Hereinafter, the garnet-type mixed metal oxide containing Li, La, Zr, and O may be referred to as "LLZ", even if it is substituted with other elements.
[0017] As described above, the phase (L) in the present invention is Li7La3Zr2O 12 Li in + Part of the site is Al 3+ and / or Ga 3+ However, it is preferable that the fluorine atom is not substituted with any element other than Al and Ga.
[0018] Furthermore, the Li-ion conductor of the present invention is characterized in that in X-ray diffraction measurement using CuKα radiation, a peak is observed at at least one of 2θ=13.8°±1° and 15.2°±1°, and it is preferable that peaks are observed at both 2θ=13.8°±1° and 15.2°±1°.
[0019] In addition, the Li ion conductor of the present invention has a cubic Li 6.25 Ga 0.25 La3Zr2O 12 Among the diffraction peaks, the diffraction peak corresponding to 2θ=30.9° is preferably observed at 2θ=30.5° or more and 30.9° or less. When LLZ is substituted with an element having an ionic radius smaller than the ionic radius of Li, La, Zr, and O, the diffraction peak corresponding to 2θ=30.9° appears shifted to a higher angle side than 30.9°, and conversely, when LLZ is substituted with an element having a larger ionic radius, the diffraction peak corresponding to 2θ=30.9° tends to appear shifted to a lower angle side than 30.9°. The diffraction peak corresponding to 2θ=30.9° preferably appears at 2θ=30.5° or more and less than 30.9°. For example, when a part of the garnet-type composite metal oxide phase (L) containing Li, La, Zr, and O is substituted with Cl element, it is considered that the diffraction peak corresponding to 2θ=30.9° appears at 2θ=30.5° or more and less than 30.9°.
[0020] The Li-ion conductor of the present invention preferably has a lattice constant of more than 12.95 Å and not more than 13.15 Å. For example, it is considered that the Li-ion conductor has such a lattice constant when a part of the garnet-type complex metal oxide phase (L) containing Li, La, Zr and O is substituted with Cl element.
[0021] As described above, in a preferred embodiment, the Li-ion conductor of the present invention can be produced using a eutectic mixture of two kinds of metal halides, and in one preferred embodiment in which Li is contained as the metal, the resulting Li-ion conductor has a metal-containing phase (K) different from the phase (L), and the phase (K) contains a halogen element and Li. In a more preferred embodiment, the phase (K) contains Li, Ta, and a halogen element.
[0022] The Li-ion conductor of the present invention has a particle assembly structure having the garnet-type composite metal oxide phase (L), and preferably has the phase (K) at the particle interfaces. The presence of the phase (K) at the particle interfaces of the phase (L) allows Li ions to be smoothly conducted from phase (L) to phase (L) via phase (K).
[0023] The Li-ion conductor of the present invention can have an activation energy Ea of 0.6 eV or less at room temperature as measured by impedance measurement, and a Li-ion conductivity σ total to 1.0×10 -7 The activation energy Ea is preferably 0.57 eV or less, more preferably 0.55 eV or less, and further preferably 0.50 eV or less, and the lower limit is not particularly limited, but is, for example, 0.25 eV. The Li ion conductivity σ total is 2.0 x 10 -7 S / cm or more is preferable, and 4.0×10 -7 More preferably, it is 1.0×10 -6 S / cm or more, more preferably 5.0×10 -6 S / cm or more, especially 1.0×10 -5 S / cm or more is preferable, and the upper limit is not particularly limited, but for example, 7.0×10-5 S / cm.
[0024] This application claims the benefit of priority based on Japanese Patent Application No. 2019-167381, filed on September 13, 2019. The entire content of the specification of Japanese Patent Application No. 2019-167381, filed on September 13, 2019, is incorporated herein by reference. EXAMPLES
[0025] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples, and can of course be modified within the scope of the above and below-mentioned aims, and all such modifications are within the technical scope of the present invention.
[0026] Example 1 Li manufactured by Toshima Manufacturing Co., Ltd. 6.25 Ga 0.25 La3Zr2O 12 100 parts by mass of a eutectic mixture of 50 parts by mass of LiCl and TaCl5 (molar ratio of LiCl and TaCl5 is 50:50, melting point: 220°C) was mixed in a mortar for 30 minutes, and the resulting mixed powder was placed in a mold and pressure of 375 MPa was applied to form a pellet with a diameter of 10 mm and a thickness of about 1 mm. Mixing in the mortar and forming the pellet were performed in a dry room. The dew point temperature in the dry room was -60°C. The formed pellet was annealed at 220°C for 15 minutes in a small electric furnace (under argon atmosphere) in a glove box (dew point temperature -90°C), and Au was sputtered on both sides of the pellet to form an electrode with a diameter of 8 mm. The obtained pellet sample was set in an all-solid-state battery evaluation cell manufactured by Hosen Co., Ltd., connected to a potentiogalvanometer, and impedance measurement was performed in the temperature range from room temperature to 100°C to evaluate the Li ion conductivity. As a result, the ion conductivity at room temperature σ total is 2.2 x 10 -5 The activation energy was calculated from an Arrhenius plot using the ionic conductivity values at each temperature. The activation energy Ea was 0.39 eV.
[0027] The annealed pellets were crushed to obtain a powder sample, and the crystal structure of the powder sample was analyzed using a Bruker XRD (X-ray Diffraction analysis) device. The results are shown in Figure 1. XRD measurements were performed using CuKα radiation at λ = 1.5418 nm and θ = 10 to 50°. Figure 1 shows that the cubic Li7La3Zr2O 12 Peaks corresponding to Li7La3Zr2O are observed at 2θ = 13.8° and 15.2°, as well as peaks corresponding to the added LiCl. 12、 Crystalline phases different from those of LiCl and TaCl5 were observed.
[0028] Examples 2 to 10 Li 6.25 Ga 0.25 La3Zr2O 12 Pellets were molded and annealed in the same manner as in Example 1, except that the type and amount of the eutectic mixture mixed with and the annealing conditions were as shown in Table 1, and the ionic conductivity and activation energy at room temperature were measured. The results are shown in Table 1. Note that only in Example 4, the measurement results at 50°C are shown.
[0029] Comparative Example 1 LiCl and TaCl5 eutectic mixture without Li 6.25 Ga 0.25 La3Zr2O 12 Except for the fact that the chisel was molded and annealed, the ionic conductivity was measured at room temperature in the same manner as in Example 1. The results are shown in Table 1.
[0030] Reference example 1 The same Li manufactured by Toshima Manufacturing Co., Ltd. as used in Example 1 was used. 6.25 Ga 0.25 La3Zr2O 12 The mixture was placed in a mold and a pressure of 375 MPa was applied to form a pellet having a diameter of 10 mm and a thickness of about 1 mm. The formed pellet was annealed in air at 1230°C for 1200 minutes, and Au was sputtered on both sides of the pellet to form electrodes having a diameter of 8 mm. Thereafter, the Li ion conductivity was measured at room temperature in the same manner as in Example 1. The results are shown in Table 1.
[0031] [Table 1]
[0032] The ionic conductor of Example 1, which was obtained by molding a mixture of LLZ and a eutectic mixture having a eutectic point of 600°C or less, and heat-treating the obtained molding at 600°C or less, exhibited good ionic conductivity as shown in Table 1. Examples 2 to 10, in which ionic conductors were produced in the same manner as in Example 1, also exhibited good ionic conductivity as shown in Table 1. On the other hand, Comparative Example 1, in which a molding of only LLZ was annealed under the same conditions as in Example 1, did not exhibit any ionic conductivity at room temperature.
[0033] FIG. 2(a) shows an SEM image of the ionic conductor of Example 1, and FIG. 2(b) shows an SEM image of the ionic conductor of Comparative Example 1. As shown in FIG. 2, in Comparative Example 1 (FIG. 2(b)) in which a eutectic mixture was not used, an LLZ grain aggregate structure was observed, and the grain boundaries were not connected. On the other hand, when FIG. 2(a) showing Example 1 is compared with FIG. 2(b), the LLZ grain structure is observed in FIG. 2(a), but a phase connecting the grain boundaries of the LLZ is observed. In addition, a peak of LiCl is observed in the XRD of FIG. 1, and considering the annealing temperature in Example 1 and the melting point of the eutectic mixture used in Example 1, it is considered that the phase connecting the grain structure of LLZ is a phase in which the eutectic mixture of LiCl and TaCl5 is melted.
[0034] Furthermore, the enlarged view of the XRD analysis result of Example 1 shown in FIG. 6.25 Ga 0.25 La3Zr2O 12 The diffraction peak corresponding to 2θ=30.9° in the ionic conductor of Example 1 is shown in Fig. 3 together with the XRD diffraction chart of Fig. 3. As shown in Fig. 3, in the ionic conductor of Example 1, the diffraction peak corresponding to 2θ=30.9° is shifted to the lower angle side, and is observed at a position of 2θ=30.5° or more and less than 30.9°.
[0035] In addition, for Examples 1 and 2, the lattice constant was calculated by determining the interplanar spacing d value from the following formulas (1) and (2) using the diffraction peak of the (400) plane obtained by the above-mentioned XRD measurement, and the result was 12.99 Å for Example 1 and 13.00 Å for Example 2. 2dsinθ=nλ (1) 1 / d 2 =(h 2 +k 2 +l 2 ) / a 2 (2) d: interplanar spacing, a: lattice constant, h, k and l: Miller indices [Industrial Applicability]
[0036] The Li-ion conductor of the present invention can be suitably used as a solid electrolyte material for secondary batteries.
Claims
1. A Li ion conductor having a garnet-type complex metal oxide phase (L) containing Li, La, Zr, and O, which has a diffraction peak at at least one of 2θ = 13.8 ° ± 1 ° and 2θ = 15.2 ° ± 1 ° in X-ray diffraction measurement using CuKα radiation, A Li ion conductor, characterized in that a diffraction peak corresponding to 2θ=30.9° among the diffraction peaks of cubic Li6.25Ga0.25La3Zr2O12 in X-ray diffraction measurement using CuKα radiation is observed at 2θ=30.5° or more and 30.9° or less.
2. A Li ion conductor as described in claim 1, which has diffraction peaks at both 2θ = 13.8° ± 1° and 2θ = 15.2° ± 1° in X-ray diffraction measurement using CuKα radiation.
3. A Li ion conductor as described in claim 1 or 2, wherein the interface of the phase (L) is connected by a eutectic mixture having a melting point of 600°C or less.
4. The Li ion conductor according to any one of claims 1 to 3, which has a metal-containing phase (K) different from the phase (L), and the phase (K) contains a halogen element and Li.
5. The Li ion conductor according to any one of claims 1 to 4, having a lattice constant of more than 12.95 Å and not more than 13.15 Å.
6. The Li ion conductor according to any one of claims 1 to 5, wherein the activation energy Ea as determined by impedance measurement is 0.6 eV or less.
7. Li ion conductivity σ at room temperature by impedance measurement total is 1.0 x 10 -7 The Li ion conductor according to any one of claims 1 to 6, having a specific conductivity of 1.5 S / cm or more.
8. A method for producing a Li ion conductor having a garnet-type complex metal oxide phase (L) containing Li, La, Zr and O, comprising the steps of: A mixture of a eutectic mixture having a melting point of 600° C. or less and a garnet-type composite metal oxide containing Li, La, Zr and O is molded, and the obtained molded product is heat-treated at 600° C. or less to connect the interface of the garnet-type composite metal oxide phase (L) using the eutectic mixture having a melting point of 600° C. or less; A method for producing a Li ion conductor, wherein the eutectic mixture is a eutectic mixture of ZrCl 4 , AlCl 3 , NbCl 5 or TaCl 5 with LiCl, or a eutectic mixture of LiF with TaF 5 .
Citation Information
Patent Citations
Garnet-type solid electrolyte, secondary battery including garnet-type solid electrolyte, and manufacturing method of garnet-type solid electrolyte
JP2012174659A
Garnet material for Li secondary battery
JP2016535391A
Ion conductor, lithium battery, and method of producing ion conductor
JP2017091788A
Solid electrolyte for all-solid type lithium secondary battery, method for manufacturing the same, and all-solid type lithium secondary battery including the solid electrolyte
JP2019029353A
